Assessing WRF-Modeled vertical profiles during MRG wave events on the southern coast of West Java: impact of vertical resolution, domain configuration, and input data - Satiadi, Didi; Trismidianto; Purwaningsih, Anis; Harjupa, Wendi; Fathrio, Ibnu; F. Andarini, Dita; Risyanto; Harjana, Teguh; S. Praja, Alfan; Noersomadi; et al. (Vietnam Journal of Earth Sciences, 2025)
Mixed Rossby-gravity (MRG) waves are key equatorial disturbances that modulate convection and rainfall across the Maritime Continent, yet their representation in regional models remains underexplored. Accurate simulation of MRG waves induced vertical structure is critical for improving forecasts of tropical weather variability and associated hydrometeorological hazards. This study evaluates the Weather Research and Forecasting (WRF) model’s ability to simulate vertical atmospheric profiles during an MRG wave event on the southern coast of West Java from 26 to 29 September 2022, using radiosonde observations at 06, 12, and 18 local time (LT). Eleven model configurations were evaluated, differing in domain schemes (two vs. three nesting steps), vertical resolution (33, 45, 60, 80, and 100 levels), and input data sources (Real-Time Global Forecast System [GFS] vs. Final Operational Global Analysis [FNL]). All model configurations used in the simulation have a fixed physics scheme parameterization. The simulations were compared with radiosonde observations and evaluated statistically using the correlation coefficient (R) and Normalized Mean Absolute Error (NMAE). The analysis demonstrates that the WRF model effectively captures MRG wave dynamics by simulating key atmospheric variables, including pressure (P), temperature (T), relative humidity (RH), zonal (U) and meridional (V) wind anomalies in strong agreement with observations. P is well represented, exhibiting the highest R (0.81), whereas RH is the lowest (0.21), likely reflecting the model’s inability to capture fine‑scale observed moisture variations. Configurations that utilized a two-step nesting domain and the FNL input demonstrated the best performance, achieving higher R values and lower NMAE. Input data had a notable impact on model performance: the FNL analysis improved R by 36% and reduced NMAE by 12% compared to GFS, likely due to FNL’s assimilation of observational data, which reduces uncertainty. Moreover, a domain scheme with a smaller outer domain and fewer nesting steps also improved R by 36% and reduced NMAE by 12%, suggesting that simpler domain configurations help limit error propagation. Additionally, increasing the vertical resolution from 33 to 100 levels enhanced the simulation of MRG wave structures, improving R by 45% and reducing NMAE by 22%. These findings enhance the understanding of MRG wave dynamics and offer valuable insights for improving regional weather forecasting.